Abiotic factors related to the incidence of the Austrocedrus chilensis disease syndrome at a landscape scale - la Manna, Ludmila Andrea (2008)
In this paper, the incidence of the A. chilensis disease syndrome in the "16 de Octubre" Valley (Chubut, Argentinean Patagonia) was related to landscape climatic, topographic and edaphic attributes, using remote sensing, geographic information systems and statistical methods. A strong relationship between the occurrence and incidence of the A. chilensis disease syndrome and site variables related to poor soil drainage was found. Non-allophanized soils with fine textures on flat and wavy soil phases, geomorphologies associated to alluvial processes, and low elevations and gentle slopes were positively related to the incidence of the disease. These relationships at a landscape scale agree with previous studies carried out at the stand level. A logistic predictive model of diseased occurrence was developed for the study area considering aspect, elevation, slope, mean annual precipitation and soil phase (classified according to predominant slopes).